The Association Between Cardiovascular Autonomic Function and Changes in Kidney and Myocardial Function in Type 2 Diabetes and Healthy Controls - Laursen, Jens Christian; Rasmussen, Ida Kirstine B.; Zobel, Emilie H.; Hasbak, Philip; von Scholten, Bernt Johan; Holmvang, Lene; Ripa, Rasmus S.; Hansen, Christian S.; Frimodt-Moeller, Marie; Kjaer, Andreas; Rossing, Peter; Hansen, Tine W. (Frontiers in Endocrinology, 2021)
Background: The mechanisms linking cardiovascular autonomic neuropathy, diabetic kidney disease and cardiovascular mortality in type 2 diabetes are widely unknown. We investigated the relationship between baseline cardiovascular autonomic function and changes in kidney and myocardial function over six years in patients with type 2 diabetes and healthy controls. Methods: Post-hoc analysis of a cohort study in 24 patients with type 2 diabetes and 18 healthy controls. Baseline determinants were cardiovascular autonomic reflex tests (heart rate response to: standing (30:15); deep breathing (E:I); and the Valsalva test) and time- and frequency-domain heart rate variability indices. Outcomes were changes in estimated glomerular filtration rate (eGFR), albuminuria, myocardial flow reserve (MFR) measured by cardiac 82Rb PET/CT, and coronary artery calcium score (CACS). Results: Mean age at inclusion was 61±10 years and 36% were female. Mean follow up time was 6±0 years. A lower response in heart rate to the Valsalva test (corresponding to weaker autonomic function) was associated with a larger decline in eGFR (p=0.04), but not significantly after adjustment for sex, baseline age, smoking status, systolic blood pressure, heart rate, HbA1c, body mass index and baseline eGFR (p=0.12). A higher baseline response in heart rate to standing (30:15) was associated with a larger decline in myocardial flow reserve in the unadjusted analysis (p=0.02) and after adjustment (p=0.02). A higher response in heart rate to the Valsalva maneuver was associated with a larger increase in CACS (p = 0.02), but the association became insignificant after adjustment (p = 0.16). Conclusion: A lower response in heart rate to the Valsalva test was associated with a larger decline in kidney function, indicating that autonomic dysfunction may predict future loss of kidney function. However, we did not find any association between lower values in cardiovascular autonomic function at baseline and a worsening in albuminuria, myocardial function, or atherosclerotic burden.